2022
DOI: 10.1186/s12933-022-01458-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30 promotes fatty acid beta-oxidation and endothelial cell dysfunction and is a circulating biomarker of coronary microvascular dysfunction in pre-clinical models of diabetes

Abstract: Background Type 2 diabetes (T2D) is associated with coronary microvascular dysfunction, which is thought to contribute to compromised diastolic function, ultimately culminating in heart failure with preserved ejection fraction (HFpEF). The molecular mechanisms remain incompletely understood, and no early diagnostics are available. We sought to gain insight into biomarkers and potential mechanisms of microvascular dysfunction in obese mouse (db/db) and lean rat (Goto-Kakizaki) pre-clinical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 70 publications
3
38
0
Order By: Relevance
“…The expression of miR-30d has been shown to be increased in diabetes. miR-30d was found to be increased in endothelial cells of the left ventricle of db/db mice, but not other organs; 36 increased in lactating mothers with type 1 diabetes; 37 increased in the serum of patients with type 2 diabetes. 38 Second, miR-30d was reported to be a glucose-regulated miRNA and could induce insulin transcription in pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The expression of miR-30d has been shown to be increased in diabetes. miR-30d was found to be increased in endothelial cells of the left ventricle of db/db mice, but not other organs; 36 increased in lactating mothers with type 1 diabetes; 37 increased in the serum of patients with type 2 diabetes. 38 Second, miR-30d was reported to be a glucose-regulated miRNA and could induce insulin transcription in pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 88%
“… 42 In addition, miR-30d was reported to promote fatty acid beta-oxidation in cardiac endothelium in type 2 diabetes mice. 36 Thus, the excessive generation of reactive lipid intermediates in cardiomyocytes may induce lipotoxicity. Without the diabetes injury, the pro-fatty acid beta-oxidation of miR-30d may benefit cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We considered miRNAs within the top 50% of abundance and cross-examined the differential expression between both survivors and non-survivors of COVID-19 as well as SARS-CoV-2 severe negatives. Additionally, we took into consideration existing biological relevance, thereby specifically analyzing miR-1, which is associated with myocardial injury, 70 , 71 miR-199a-3p which has been shown to be cardioprotective, 72 miR-181a-5p which has been shown to restrict vascular inflammation, 73 along with members of the miR-30 family which are enriched in ECs and capable of modulating inflammation, 74 , 75 , 76 as well miR-339-3p and miR-6080 which were among the highest differentially expressed. Univariable hazard ratios and log-rank P-values were generated to determine the relationship of the miRNA expression measured in plasma with mortality.…”
Section: Resultsmentioning
confidence: 99%
“…We selected 12 miRNAs associated with diabetic HF. The initial selection of miRNAs in our panel were miR-1 [ 28 , 29 ], miR-21 [ 30 ], miR-29a [ 31 ], miR-30d [ 32 , 33 ], miR-34a [ 34 ], miR-126a [ 35 ], miR-143 [ 36 ], miR-145 [ 37 ], miR-195 [ 38 ], miR-206 [ 39 ], miR-320 [ 39 ] and miR-378 [ 40 ]. We found that the expression of all miRNAs was significantly lower in HFpEF diabetic hearts than in controls ( Figure 5 A–L).…”
Section: Resultsmentioning
confidence: 99%